Refractile bodies of Eimeria tenella are proteinaceous membrane-less organelles that undergo dynamic changes during infection - Burrell, Alana; Marugan-Hernandez, Virginia; Graefin Von Der Recke, Karolin; Aguiar-Martins, Kelsilandia; Gabriel, Heloisa Berti; Tomley, Fiona M.; Vaughan, Sue (Frontiers in Cellular and Infection Microbiology, 2023)
Refractile bodies (RB) are large membrane-less organelles (MLO) of unknown function found as a prominent mismatched pair within the sporozoite stages of Eimeria parasitic protozoa. Time-lapse live confocal microscopy of MDBK cells infected with E. tenella sporozoites confirmed previous reports that RB reduce from two to one post-infection and showed that reduction in RB number occurs via merger of the anterior RB with the posterior RB, a process that lasts 20-40 seconds and takes place between 2 and 5 hours post-infection. Ultrastructural studies using serial block face-scanning electron microscopy (SBF-SEM) of whole individual sporozoites, both pre- and post-host cell invasion, confirmed the live cell imaging of RB number changes and showed also that changes to the overall cell body shape accompanied RB merger. Furthermore, the single RB was found to be larger in volume post-merger than the two RB pre-merger. MLOs in eukaryotic organisms are characterised by their lack of a membrane and ability to undergo liquid-liquid phase transitions and fusion. Due to the proposed role of actin in this process, and the shape changes in parasite cell body we observed at the time of RB merger, actin inhibitors were used to investigate a potential role for actin in RB merger. Cytochalasin D significantly inhibited RB merger and had a significant effect on cell body shape, thus we propose that RB are classed as an MLO and recognised as one of the largest MLOs so far characterised.